SEISMIC REACTION OF NONLINEAR SYSTEM OF SEISMIC DEFENSE WITH KINEMATIC SUPPORTS - A. D. Abakarov; H. R. Zajnulabidova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the study is to obtain formulae for calculating probability of seismic response characteristics of nonlinear seismic isolation system with the specified function "force-shifting", characteristic of seismic isolation system with kinematic pillars and score the effectiveness of this system of seismic isolation in multi-storey buildings.Method. The studies were performed analytical techniques and numerical method of statistical tests.Result. Analytical expressions to calculate the mean square value of one massive seismic isolation system with displacement kinematic pillars and the effectiveness of the application of graphs of kinematic seismic isolation bearings for multi-storey buildings based on the results of numerical experiments using the method of statistical tests.Conclusion. Application of kinematic supports, with "power-move" described by the specified in the work of a non-linear function, allows you to reduce the seismic loads on buildings and distortions of floors 2 or more times. Kinematic bases are more effective when high-frequency effects and in the buildings of the constructive solution of a height of not more than 5 floors.